Worldwide spatiotemporal atmospheric ammonia (NH3) columns variability revealed by satellite. Issue 20 (19th October 2015) - Van Damme, M.; Erisman, J. W.; Clarisse, L.; Dammers, E.; Whitburn, S.; Clerbaux, C.; Dolman, A. J.; Coheur, P.‐F.
Abstract: We exploit 6 years of measurements from the Infrared Atmospheric Sounding Interferometer (IASI)/MetOp‐A instrument to identify seasonal patterns and interannual variability of atmospheric NH3 . This is achieved by analyzing the time evolution of the monthly mean NH3 columns in 12 subcontinental areas around the world, simultaneously considering measurements from IASI morning and evening overpasses. For most regions, IASI has a sufficient sensitivity throughout the years to capture the seasonal patterns of NH3 columns, and we show that each region is characterized by a well‐marked and distinctive cycle, with maxima mainly related to underlying emission processes. The largest column abundances and seasonal amplitudes throughout the years are found in southwestern Asia, with maxima twice as large as what is observed in southeastern China. The relation between emission sources and retrieved NH3 columns is emphasized at a smaller regional scale by inferring a climatology of the month of maximum columns. Key Points: Six years of NH3 morning and evening IASI measurements are analyzed Seasonal cycles of atmospheric NH3 are characterized for subcontinental areas Source processes are attributed from a climatology of the month of NH3 maximum